Case reportOmalizumab in pregnant women treated due to severe asthma: two case reports of good outcomes of pregnancies - Kupryś-Lipińska, Izabela; Tworek, Damian; Kuna, Piotr (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
The article presents case reports of 2 women who became pregnant during therapy with omalizumab. Both subjects suffered from very severe asthma and were treated chronically with all available medications including systemic steroids (first – 20 mg prednisolone/day, second – 40 mg prednisolone/day). Both were enrolled into treatment with omalizumab and started regular therapy in 2007. The course of asthma significantly improved in both cases (withdrawal of oral steroids or significant reduction of their dose, better asthma control). The first woman, 32-year-old, became pregnant in 2010 and gave birth in Oct 2010 – it was her 3 rd pregnancy, and 3 rd labor. The second woman, 31-year-old, also became pregnant in 2010 and gave birth in Jan 2011 – it was her 5 th pregnancy and 2 nd labor. Both had severe asthma exacerbations during previous pregnancies and labors, and decided to continue therapy with omalizumab. The first woman, besides omalizumab, was treated with high doses of inhaled corticosteroids (ICS) and long-acting β agonists (LABA) while the second one was treated with high doses of ICS, LABA and 2.5 mg to 5 mg prednisone/day. The pregnancies proceeded without asthma exacerbations. The first woman delivered a healthy girl (Apgar 9, weight 3200 g, length 56 cm) in the 40 th week of pregnancy by caesarean section due to the narrow pelvis. The second one delivered a healthy boy (Apgar 9, weight 3800 g, length 56 cm) in week 40 by caesarean section due to the aggravating obstetrical history. In both cases, treatment with omalizumab did not affect pregnancies and newborns.